2015
DOI: 10.1007/s00170-015-7517-0
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel bulk plastic deformation method: hydrostatic backward extrusion

Abstract: This paper aimed to propose a novel bulk plastic deformation method entitled hydrostatic backward extrusion process that is an implementation of the benefits of hydrostatic extrusion to the backward extrusion process. The applicability of the process was investigated using experimental tests and finite element analysis. The results showed that the produced tube by hydrostatic backward extrusion exhibits higher effective plastic strain while needing lower process load (elimination of friction force). The maximu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The method was applied to commercial Al and significant grain refinement and improvement in strength were obtained by Hosseini et al . 77 A hydrostatic-based process called ‘hydrostatic back extrusion’, presented by Manafi et al ., 125 may be more suitable for processing hard-to-deform and brittle materials. 126128
17 Schematic of the new backward extrusion process 78
…”
Section: Spd Processes Suitable For Tubular Samplesmentioning
confidence: 99%
“…The method was applied to commercial Al and significant grain refinement and improvement in strength were obtained by Hosseini et al . 77 A hydrostatic-based process called ‘hydrostatic back extrusion’, presented by Manafi et al ., 125 may be more suitable for processing hard-to-deform and brittle materials. 126128
17 Schematic of the new backward extrusion process 78
…”
Section: Spd Processes Suitable For Tubular Samplesmentioning
confidence: 99%
“…Peng et al [12], by calculating the stress distribution in Nb/Cu composited by HE, investigated its interface bonding status. Manifi et al [13] improved conventional backward extrusion by employing HE principles to reduce the extrusion load; the maximum load was reduced by 80% compared to the conventional back extrusion process. Kopp and Barton [14] improved the model of HE and analyzed the differences between experimentation and simulation.…”
Section: Fem Methods and Materialsmentioning
confidence: 99%
“…Kopp and Barton [14] improved the model of HE and analyzed the differences between experimentation and simulation. The comparisons between the simulation and experiment were discussed in [10][11][12][13][14], but the comparison between the different simulation models has not been discussed in detail yet. In the present study, the pressure-load mode and displacement-load mode are used to simulate the HE process.…”
Section: Fem Methods and Materialsmentioning
confidence: 99%
“…Finite element (FE) simulation by Shatermashhadi et al [10] showed well that the obtained effective strain of the new method was more than twice that of the conventional BE method. Furthermore, Manafi et al [11] introduced hydrostatic pressure in the ACAE to further increase the effective plastic strain and reduce the force load. Also, the feasibility of the process has been verified by the production of pure Al test part [12], and the extruded part achieved evident grain refinement in comparison with the initial material.…”
Section: Introductionmentioning
confidence: 99%